Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.5935/abc.20170081
|View full text |Cite
|
Sign up to set email alerts
|

Gestational Protein Restriction Increases Cardiac Connexin 43 mRNA levels in male adult rat offspring

Abstract: BackgroundThe dietary limitation during pregnancy influences the growth and development of the fetus and offspring and their health into adult life. The mechanisms underlying the adverse effects of gestational protein restriction (GPR) in the development of the offspring hearts are not well understood.ObjectivesThe aim of this study was to evaluate the effects of GPR on cardiac structure in male rat offspring at day 60 after birth (d60).MethodsPregnant Wistar rats were fed a normal-protein (NP, 17% casein) or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 41 publications
(48 reference statements)
0
7
0
Order By: Relevance
“…This is the first demonstration of adult neurogenic hypertension programmed in the peri-pubertal period, while other studies have addressed the effect of low protein diet on blood pressure just after the exposure to the insult ( Loss et al, 2007 ; Penitente et al, 2007 ; Del Carmen Miñana-Solis and Escobar, 2008 ; Martins et al, 2011 ; Murca et al, 2012 ; Gomide et al, 2013 ; Penitente et al, 2014 ; Cappelli et al, 2018 ). In the context of DOHaD concept the studies have explored an earlier susceptible window of development, the peri-natal period ( Latorraca et al, 1998 ; De Oliveira et al, 2011 ; De Brito Alves et al, 2014 ; De Oliveira et al, 2014 ; Nascimento et al, 2014 ; Barros et al, 2015 ; De Oliveira et al, 2016 ; Ferreira et al, 2016 ; Paulino-Silva and Costa-Silva, 2016 ; Rossini et al, 2017 ; Barros et al, 2018 ; Martins et al, 2018 ; Assalin et al, 2019 ; Ferreira et al, 2019 ). The exact stimulus to the neurogenic hypertension is difficult to determine as the LP animals were hypophagic during the period of protein restriction, which also induced a caloric-restriction in peri-puberty, and a critical window of development ( De Oliveira et al, 2013 ; De Oliveira et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This is the first demonstration of adult neurogenic hypertension programmed in the peri-pubertal period, while other studies have addressed the effect of low protein diet on blood pressure just after the exposure to the insult ( Loss et al, 2007 ; Penitente et al, 2007 ; Del Carmen Miñana-Solis and Escobar, 2008 ; Martins et al, 2011 ; Murca et al, 2012 ; Gomide et al, 2013 ; Penitente et al, 2014 ; Cappelli et al, 2018 ). In the context of DOHaD concept the studies have explored an earlier susceptible window of development, the peri-natal period ( Latorraca et al, 1998 ; De Oliveira et al, 2011 ; De Brito Alves et al, 2014 ; De Oliveira et al, 2014 ; Nascimento et al, 2014 ; Barros et al, 2015 ; De Oliveira et al, 2016 ; Ferreira et al, 2016 ; Paulino-Silva and Costa-Silva, 2016 ; Rossini et al, 2017 ; Barros et al, 2018 ; Martins et al, 2018 ; Assalin et al, 2019 ; Ferreira et al, 2019 ). The exact stimulus to the neurogenic hypertension is difficult to determine as the LP animals were hypophagic during the period of protein restriction, which also induced a caloric-restriction in peri-puberty, and a critical window of development ( De Oliveira et al, 2013 ; De Oliveira et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…A similar profile was observed by Ferreira et al (2019) , who showed that carbonylated proteins and SOD were decreased, while malonildialdehyde, a lipid peroxidation marker, and glutathione transferase enzyme were increased in the brainstem in PN150 rats exposed to perinatal protein restriction ( Ferreira et al, 2019 ). Oxidative stress is a mechanism involved in the sympathetic arousal generated from the brainstem and resulting in cardiac remodeling ( Rossini et al, 2017 ; Assalin et al, 2019 ). Therefore, the present disorganization of the redox state must be better explored to assess its role as a mediator of the observed dysfunctions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this research, the histomorphometric measurements were performed using the Image J 1.51, Java 1.8.0_101 (64-bit) digital image analysis software. This program is widely used in scientific research involving quantification and analysis of images [5][6][7][8][9][10] , with programming platform based on the Java language. In a systematic way, all the photomicrographs were processed according to the same algorithm.…”
Section: ■ Introductionmentioning
confidence: 99%